Influence of Dividend Payout Ratio on Share Prices of Quoted Companies in Nigeria: Array - Ojogbo, Samuel; Oke, Babatunde; Mustapha, Isiaka (Acta Universitatis Danubius. Œconomica, 2022)
This research investigates the influence of dividend pay-out ratio on share prices of quoted companies on the Nigeria Stock Exchange (NSE) between 2014 and 2020 across fifteen (15) companies. panel least square estimation, through the use of Hausman’s test, was used to analyze the data. In the econometric model, dependent variable (proxy by the market share price) was regressed on the following explanatory variables of earning per share, dividend yield, return on investment, dividend payout ratio, and retention rate. This research discovered a joint significant relationship between earning per share, dividend yield, return on investment, dividend payout ratio, retention rate and market share prices. This research therefore recommends that; Furtherance to the findings of this research, firms may be well aware that dividend payment may not necessarily be a factor that affect market share price.